2002
DOI: 10.1046/j.1365-2664.2002.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest‐site limitation and density dependence of reproductive output in the common goldeneyeBucephala clangula: implications for the management of cavity‐nesting birds

Abstract: Summary1. Hole-nesting birds are frequently faced with a shortage of suitable nest sites in regions of intensive forest management. Nest boxes are sometimes provided to alleviate nest-site limitation in cavity-nesting waterfowl and are also recommended for several rare and endangered species. However, the impacts on effective breeding numbers and breeding success have rarely been considered, particularly in instances where density dependence might operate. 2. We experimentally manipulated nest sites to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 57 publications
2
29
0
5
Order By: Relevance
“…Locating natural cavity nests can be challenging in some habitat types (e.g., Vaillancourt et al 2009), population density can be colimited by other factors, e.g., intraspecific competition for food, birds can switch from occupying natural nesting sites to artificial boxes (e.g., Gauthier and Smith 1987), or nest box deployment can coincide with other larger scale, sometimes continental, factors that dictate population sizes. Few studies have attempted to demonstrate using experimentation the connection between various measures of breeding activity, the availability of nest boxes, and whether nest box deployment influence population size (Savard 1988, Newton 1994, Pöysä and Pöysä 2002.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Locating natural cavity nests can be challenging in some habitat types (e.g., Vaillancourt et al 2009), population density can be colimited by other factors, e.g., intraspecific competition for food, birds can switch from occupying natural nesting sites to artificial boxes (e.g., Gauthier and Smith 1987), or nest box deployment can coincide with other larger scale, sometimes continental, factors that dictate population sizes. Few studies have attempted to demonstrate using experimentation the connection between various measures of breeding activity, the availability of nest boxes, and whether nest box deployment influence population size (Savard 1988, Newton 1994, Pöysä and Pöysä 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Observed reductions in numbers of broods and brood sizes in 2004 because of nest box closure were not accompanied by estimates of population size on the Buffalo Lake Moraine. Rigorous examinations of linkages between availability of nesting sites and population size require substantive experimental designs where the manipulation occurs across large spatial scales and over multiple years, and have been rarely completed (but see Pöysä and Pöysä 2002). Our study provides indirect evidence that nest box deployment influences population sizes of Bufflehead and Common Goldeneye by demonstrating (1) 3-to 10-fold reductions in numbers of broods and brood sizes because of nest box closure, (2) increases in occurrence and density over a 16-year period coinciding with nest box deployment, and (3) local increases in populations of the two species on Buffalo Lake Moraine that were not simple manifestations of increases in the size of regional populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nest sites and the relative safety they provide to eggs, nestlings, and attendant adults are an important component of life-history strategies in birds (Martin and Li 1992) and have also been important targets for conservation efforts (Eskowich et al 1998, Pöysä and Pöysä 2002, Arnold et al 2007). Mallards (Anas platyrhynchos) have highly flexible nest-site selection, but the vast majority of females nest on the ground in upland habitats, thereby exposing themselves to a large suite of terrestrial mammalian predators to which they are otherwise immune (Sargeant et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Hole-nesting birds are considered as one of the most susceptible groups to such impacts due to their strong dependence on trees (Angelstam & Mikusiński 1994, Martin & Eadie 1999, Imbeau et al 1999. It has been suggested that the availability of nesting holes limits the population density of such birds in many managed forests (von Haartman 1957, Johnson 1994, Newton 1994, Semel & Sherman 2001, Twedt & Henne-Kerr 2001, Pöysa & Pöysa 2002. Since the 1990s, with the emergence of ecological forestry, there is an increasing need to improve our understanding of biodiversity and its maintenance in natural forests, so that such knowledge can be incorporated into management guidelines (Hansen et al 1991, Fujimori 2001.…”
Section: Introductionmentioning
confidence: 99%